The Implementation of Rewards and Punishment on the Students' Motivation in English Learning at Junior High School of SMPN 7 Mataram Academic Year 2022/2023 - Sulis Viana; Ahmad Junaidi; Agus Saputra (Program Studi Pendidikan Bahasa Inggris, 2023)
This research aimed to find out the implementation of rewards and punishment on the students’ motivation in English learning at eighth grade students’ of SMPN 7 Mataram in academic year 2022/2023. This study used a descriptive qualitative approach. The sampling technique consisted purposive sampling, which included 4 English teachers, and 40 students. The data was collected involved observations, interviews, and questionnaires. The researcher utilized data collection, data reduction, data display, and conclusion as analysis techniques. The results showed that the teachers respond positively to the students who showed a lack of motivation by conducting monitoring students’ behavior and their participation during learning process. Rewards and punishment were applied should be consider the condition and situation occurred in the classroom. Meanwhile, the teachers applied punishment by understanding the characteristics of each student so they did not feel uncomfortable, or disturbed their psychological. giving rewards made the students more diligent was 70%. 95% students were happy with rewards. Meanwhile, 87.5% students more responsible, and 82.5% students obey the rules and behave well. Therefore, it can be inferred that learning motivation has increased, and the students’ undesirable behavior has decreased.